2014
DOI: 10.1021/jf503992y
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine Derivatives as Insecticides. Part 1: Synthesis and Toxicity of Some Pyridine Derivatives Against Cowpea Aphid, Aphis craccivora Koch (Homoptera: Aphididae)

Abstract: Five pyridine derivatives, namely, N-morpholinium 7,7-dimethyl-3-cyano-4-(4'-nitrophenyl)-5-oxo-1,4,5,6,7,8-hexahydroquinoline-2-thiolate (1), sodium 5-acetyl-3-amino-4-(4'-methoxyphenyl)-6-methylthieno[2,3-b] pyridine-2-carboxylate (2), piperidinium 3,5-dicyano-2-oxo-4-spirocyclopentane-1,2,3,4-tetrahydropyridine-6-thiolate (3), piperidinium 5-acetyl-3-cyano-4-(4'-methoxyphenyl)-6-methylpyridine-2-thiolate (4), and piperidinium 5-acetyl-4-(4'-chlorophenyl)-3-cyano-6-methyl-pyridine-2-thiolate (5) were prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 15 publications
3
42
0
Order By: Relevance
“…The activity concerning compound 4 may be due to the existence of the chlorine atom attached to the pyrimidine cycle in its molecular structure. Our research demonstrated that the new pyrimidothienotetrahydroisoquinoline derivatives containing pyridine moiety could effectively control cowpea aphids, A. craccivora , and this emphasis our studies done before [18,19]. These results are hopeful and valuable for additional work on the improvement of new and other potent pesticides.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The activity concerning compound 4 may be due to the existence of the chlorine atom attached to the pyrimidine cycle in its molecular structure. Our research demonstrated that the new pyrimidothienotetrahydroisoquinoline derivatives containing pyridine moiety could effectively control cowpea aphids, A. craccivora , and this emphasis our studies done before [18,19]. These results are hopeful and valuable for additional work on the improvement of new and other potent pesticides.…”
Section: Resultssupporting
confidence: 58%
“…Inspired by our promising results described in the first and second parts and as a continuation of our earlier research work aimed to find heterocycles containing pyridine moiety with expected toxicological activities [18,19], we reported here the study of the toxicity of the prepared compounds containing the previous features of neonicotinoid insecticides against cowpea Aphid, Aphis craccivora Koch encouraged to discover heterocyclic compounds with high biological effect and without environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that heterocyclic compounds, especially pyridine derivatives, are widely used and different important applicationsfor these compounds have been previously reported. [1][2][3][4][5][6] So, the chemists around the world focused on the synthesis and the applications of these compounds. Some neonicotinoids contain pyridine moiety in their structure.…”
Section: Introductionmentioning
confidence: 99%
“…Functionally substituted‐pyridines are bioactive small molecules possess a wide range of applications . Accordingly, a number of powerful synthetic strategies have been developed to effectively access this heterocyclic family .…”
Section: Introductionmentioning
confidence: 99%